FEM Structural Analysis for Ship's Beam Modification: A Case Study - Popa, Adrian; Manea, Mihaela-Greti; Ristea-Komornicki, Marian-Valentin (Engineering, Technology & Applied Science Research, 2024)
Classification is mandatory for all seagoing ships engaged in international trade worldwide, with regulations that require the strength of the hull construction to be confirmed. Upon completion of the ship's construction or during the execution of repair works in shipyards (reconversion works, modification of panels, replacement of equipment, etc.), the strength structure of the ship may be affected and the classification society must certify that it meets the requirements. Replacing old equipment sometimes implies some variations in overall dimensions, which may impose some changes (adjustments) on the layout of structural panel elements. This study applied the Finite Element Method (FEM) considering the von Mises theory in a case study of a beam modification with the support of the ANSYS software. This study used the reverse engineering method to investigate an already implemented solution.